Analysis of blended learning teaching model at Andalus Islamic Education Center Singapore - Mohamed Amin, Mohamed Hamzah Bin (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2023)
During the pandemic, Andalus Islamic Education Center implemented a learning process that adhered to the Singapore government’s Home Based Learning policy. Based on the Ministry of Singapore’s strategic direction, this institution began to transform learning. This essay attempts to assess the Blended Learning approach utilized in Islamic educational institutions in Andalusia by examining its merits and flaws. This study employs a qualitative technique, as well as a literature and field study research model. The information came from the Andalus Islamic Education Institute in the form of records, archives, or observation and interviews. With an educational analytical perspective, the data was analyzed using content analysis and descriptive analysis. The blended learning teaching process utilized at Andalusia Islamic Education was discovered to have a 50/50% teaching composition, with 50% for face-to-face activities and 50% for online learning activities. The process’s strengths and weaknesses are based on two policy principles: the main priorities relating to the health and safety of students, educators, education personnel, families, and communities, as well as student growth and development and psychosocial conditions during the Covid-19 pandemic. Abstrak Di masa pandemi, Pusat Pendidikan Islam Andalus melakukan proses pembelajaran yang menyesuaikan dengan kebijakan home based learning yang dikeluarkan oleh pemerintah Singapura. Lembaga ini mulai memodifikasi pembelajaran berbasis arah kebijakan Kementerian Singapura. Artikel ini mencoba untuk menganalisis model blended learning yang digunakan di lembaga pendidikan Islam Andalus dengan melihat kekuatan dan kelemahannya. Penelitian ini menggunakan pendekatan kualitatif dengan model penelitian kepustakaan dan studi lapangan. Data-data diperoleh dari Lembaga Pendidikan Islam Andalus, baik berupa dokumen, arsip, ataupun melalui observasi dan wawancara. Sedangkan analisis datanya menggunakan analisis isi dan analisis deskriptif dengan sudut pandang analisis pendidikan. Hasilnya didapat bahwa proses pengajaran blended learning yang digunakan di Pusat Pendidikan Andalusia menggunakan komposisi pengajaran 50/50%, yaitu 50% untuk kegiatan tatap muka (face to face) dan 50% untuk kegiatan pembelajaran online. Kekuatan dan kelemahan proses ini dilandasi oleh dua prinsip kebijakan, yaitu prioritas utama yang berkaitan dengan kesehatan dan keselamatan peserta didik, pendidik, tenaga kependidikan, keluarga, dan masyarakat; serta tumbuh kembang para pelajar dan kondisi psikososial selama masa pandemi Covid-19.